Study of Bullet Marks on Metal from a .357 Magnum Revolver at Difference Distances and Angles - กุลนิเทศ, ผู้ช่วยศาสตราจารย์พิเศษ พลตำรวจโท ดร.ณรง; บุญจงรักษ์, ลัดดาวัลย์ (Journal of Food Health and Bioenvironmental Science, 2016)
A study of bullet marks on metal from a .357 magnum revolver at different distances and angles was conducted to examine the bullet marks produced on a four door pick-up truck from a .357 magnum revolver discharged at different angles and distances. The revolver was discharged from four distances - point blank, 1, 5, and 10m - and six angles - 90 ํ, 75 ํ, 60 ํ, 45 ํ, 30 ํ and 10 ํ. Shots fired from a 90 ํ angle produced circular holes of equivatent size to the bullet. Shots fired at 75 ํ, 60 ํ, 45 ํ and 30 ํ angles resulted in oval holes with widths larger than the bullet’s size. In the case of an angle of 10 ํ, metal plate dents and scuff marks appeared which could be explained by the bullet’s mass weight combined with the kinetic energy. Thus, rather than penetrate the target, the bullet ricocheted. The average width of the gunshot entrance holes tended to increased when firing angle decreased. This research demonstrated that trajectory, bullet size, and angle of discharge affect the gunshot’s characteristics. Distances also had small effects on bullet marks.